Association between leptin gene rs7799039 polymorphism and lipid profile changes induced by isotretinoin treatment in acne patients - Khabour OF; Alzoubi KH; Firoz AS; Al-Awad RMM (Dove Medical Press, 2018)
Omar F Khabour,1,2 Karem H Alzoubi,3 Abdul Samad Firoz,1,4 Rafat MM Al-Awad2 1Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, Taibah University, Madinah, Saudi Arabia; 2Department of Medical Laboratory Sciences, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Clinical Pharmacy, Jordan University of Science and Technology, Irbid, Jordan; 4Center for Genetics and Inherited Diseases, Faculty of Medicine, Tabiah University, Madinah, Saudi Arabia Introduction: Isotretinoin, a vitamin A-derived medication, is one of the effective treatments for severe acne. However, in a fraction of patients, this treatment causes significant adverse effects. Leptin is a pro-inflammatory cytokine that plays a role in apoptosis of adipose cells and sebaceous lipid metabolism. Thus, genetic polymorphisms in the leptin (LEP) gene may modulate the response to isotretinoin therapy. Here, we explore the contribution of rs7799039 polymorphism of the LEP gene in the adverse effects of the oral isotretinoin therapy among acne patients. Materials and methods: Clinical parameters were obtained from 200 patients before and after isotretinoin treatment for acne. In addition, circulatory lipid profile and aspartate transaminase (AST) and alanine aminotransferase (ALT) enzymes from acne subjects before and 1 month after oral isotretinoin treatment were also measured. Results: An association between the rs7799039 polymorphism and the following lipid parameters: high-density lipoprotein (HDL) at baseline and after treatment, HDL % change, low-density lipoprotein % change and total cholesterol % change (P < 0.05). In addition, there was an association between the LEP polymorphism and higher AST and ALT at baseline and after treatment (P < 0.05). Conclusion: In conclusion, rs7799039 LEP polymorphism might modulate lipid parameters and liver enzymes, but not other major side effects of oral isotretinoin therapy. Keywords: leptin, isotretinoin, acne, polymorphism, side effects